2000
DOI: 10.1016/s0014-5793(00)01153-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Arabidopsis AtAMT2, a novel ammonium transporter in plants

Abstract: We have cloned and characterized the first member of a novel family of ammonium transporters in plants: AtAMT2 from Arabidopsis thaliana. AtAMT2 is more closely related to bacterial ammonium transporters than to plant transporters of the AMT1 family. The protein was expressed and functionally characterized in yeast. AtAMT2 transported ammonium in an energy-dependent manner. In contrast to transporters of the AMT1 family, however, AtAMT2 did not transport the ammonium analogue, methylammonium. AtAMT2 was expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(51 citation statements)
references
References 28 publications
3
46
0
2
Order By: Relevance
“…Whether ammonium or ammonia is the actual substrate species transported by AmtB was not determined. A similar set of ammonium transport proteins was found in Rhodobacter sphaeroides, where an ammonium-specific uptake system together with a methylammonium\ammonium permease was found (Cordts & Gibson, 1987), and in Arabidopsis thaliana where AMT1 proteins transport (methyl)ammonium (Gazzarrini et al, 1999) whilst AtAMT2 is ammoniumspecific (Sohlenkamp et al, 2000). Furthermore, the kinetic results of ammonium uptake studies indicated the presence of an additional, low-affinity ammonium transport system in C. glutamicum.…”
Section: Discussionsupporting
confidence: 56%
“…Whether ammonium or ammonia is the actual substrate species transported by AmtB was not determined. A similar set of ammonium transport proteins was found in Rhodobacter sphaeroides, where an ammonium-specific uptake system together with a methylammonium\ammonium permease was found (Cordts & Gibson, 1987), and in Arabidopsis thaliana where AMT1 proteins transport (methyl)ammonium (Gazzarrini et al, 1999) whilst AtAMT2 is ammoniumspecific (Sohlenkamp et al, 2000). Furthermore, the kinetic results of ammonium uptake studies indicated the presence of an additional, low-affinity ammonium transport system in C. glutamicum.…”
Section: Discussionsupporting
confidence: 56%
“…In Arabidopsis there are 6 AMT genes, while rice (Oryza sativa) has 10, and more detailed sequence comparisons have identified two distinct groups within the AMT family, denoted AMT1 and AMT2 (Shelden et al, 2001;Sohlenkamp et al, 2000). Like the NO − 3 transporters, some AMT1-type genes are expressed in root hairs, suggesting that they have a role in uptake of NH + 4 from the soil (Lauter et al, 1996;Ludewig et al, 2002).…”
Section: Ammonium Transportersmentioning
confidence: 99%
“…The experiment was repeated twice and representative results of one experiment are shown (average values ± interval of confidence calculated for a P value of 0.05). Different letters represent a significant difference of the means at P=0.05, according to Fisher's LSD test five members of AtAMT1 gene family and the AtAMT2 gene, all six coding for NH 4 + transporters (Ninneman et al 1994;Gazzarrini et al 1999;Sohlenkamp et al 2000;von Wiren et al 2000).…”
Section: Fig 5 A-d Effects Of Nomentioning
confidence: 99%